ENHANCING LABOUR PRODUCTIVITY IN MULTI STOREY BUILDING CONSTRUCTION - Radhakrishnan, S; Selvan, K G (International Journal of Engineering Technologies and Management Research, 2017)
The Construction Industry, which was badly hit by the demonetisation, is getting back to normalcy with construction activities coming up in full swing. Chennai City and its outskirts are buzzed with building work from small apartments to tall towers. Next to agriculture, construction industry is the source of employment for a large number of people, mostly uneducated. The piquant situation is that in some parts of the state the activities have come to a “slow going” due to paucity of river sand and whereas in the City and its outskirts, the work is going on uninterrupted. While the small builders are worst hit by the non-availability of river sand, the big builders manage the activities. The reason is that they have rate contract with two to three large suppliers for sand. Moreover, they are also using M Sand in the construction activities.